Evaluating CBT clinical competence with standardised role plays and patient therapy sessions - Liness, S; Beale, S; Lea, S; Byrne, S; Hirsch, CR; Clark, DM (Springer, 2019)
Standardised role-plays (SR) have been proposed as an alternative to recordings of patients’ therapy sessions (PTS) to assess therapist competence during CBT training. This study compared the following properties of SR assessments with established PTS assessments: interrater reliability, responsiveness to training, convergent validity of competence ratings, and predictive validity for academic outcomes. SR and PTS were both rated using the Cognitive Therapy Scale Revised (CTS-R) to assess CBT trainees’ (n = 88) level of competence at the beginning and end of training, and at one-year follow-up. Both methods demonstrated excellent inter-rater reliability between pairs of course tutors (ICC range = .81–.93) and good reliability between tutors and an external assessor (ICC range = .71–.74). CTS-R scores for both SR and PTS increased across training to reach the competence threshold and remained stable at follow-up. However, there was only a weak relationship between the two assessment methods. Further refinement of SR as a CBT assessment method is indicated.